(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The article is devoted to the scientific substantiation and study of the influence of a teenager’s sibling status on interpersonal relationships with peers. The article also describes the peculiarity of the behavior of adolescents from different sibling positions in a conflict situation.